2017
DOI: 10.3390/polym9100502
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Al2O3 Nano-Structure Functional Film on a Cellulose Insulation Polymer Surface and Its Space Charge Suppression Effect

Abstract: Cellulose insulation polymer (paper/pressboard) has been widely used in high voltage direct current (HVDC) transformers. One of the most challenging issues in the insulation material used for HVDC equipment is the space charge accumulation. Effective ways to suppress the space charge injection/accumulation in insulation material is currently a popular research topic. In this study, an aluminium oxide functional film was deposited on a cellulose insulation pressboard surface using reactive radio frequency (RF) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 51 publications
2
21
0
Order By: Relevance
“…By plotting the maximum curve slope and its intercept with the energy axis (F(R) = 0), the energy band gap value was calculated. The results showed that band gaps of 4, 3.87, 3.62, and 3.42 eV were obtained for pure and doped samples at 0, 1, 3, and 5% impurities, respectively, which it is smaller than compared to the results obtained by other researchers (E g = 7 eV) . The reason for the decrease in energy band gap following increase in the doping percentage can be adduced to the sp‐d interactions of the energy band of the d electrons of the Fe 3+ dopant band and the band electrons in Al 2 O 3 .…”
Section: Resultsmentioning
confidence: 78%
“…By plotting the maximum curve slope and its intercept with the energy axis (F(R) = 0), the energy band gap value was calculated. The results showed that band gaps of 4, 3.87, 3.62, and 3.42 eV were obtained for pure and doped samples at 0, 1, 3, and 5% impurities, respectively, which it is smaller than compared to the results obtained by other researchers (E g = 7 eV) . The reason for the decrease in energy band gap following increase in the doping percentage can be adduced to the sp‐d interactions of the energy band of the d electrons of the Fe 3+ dopant band and the band electrons in Al 2 O 3 .…”
Section: Resultsmentioning
confidence: 78%
“…Carbon XPS spectrum was characterized as shown in Figure (c) where typical sp2 hybrid and sp3 hybrid structures of C 1s gave peaks at 284.05 and 285.8 eV. Another peak at 288.4 eV corresponds to groups containing oxygen on surface of carboxyl groups, respectively . Oxygen O 1s as shown in Figure (d), has a major peak at 531.2 and shoulder at 532.3 eV that is attributed to the oxygen in hydroxyl groups…”
Section: Resultsmentioning
confidence: 99%
“…The diffractogram does not contain discrete patterns which could expose the presence of crystalline entities, including Al 2 O 3 . The absence of peaks for Al 2 O 3 phase is due to the amorphous texture [ 26 ]. Instead, a plain background is recorded, with high low-angle intensity decreasing at higher theta angles.…”
Section: Resultsmentioning
confidence: 99%